Submental intubation in complex craniomaxillofacial trauma cases - Navin Kumar, A.; Chattopadhaya, P. K.; Dua, Gaurav; Mehta, Sandeep (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Background: Airway management in patient with craniomaxillofacial trauma is challenging due to disruption of components of upper airway. In complex panfacial trauma cases, especially involving naso-orbito-ethmoidal complex, the airway is shared between the maxillofacial surgeon and anaesthesiologist. Often in such severe trauma cases, both nasotracheal and orotracheal intubation are contraindicated. Previously in such situation tracheostomy was the method of choice. Though tracheostomy is time tested it has its fair share of complications, some even life threatening. Other methods were used such as retromolar intubation as an alternative, but it may not be suitable for all such cases. Another approach is submental intubation but not so much in routine practice. A retrospective study was designed to evaluate clinical criteria’s airway management in complex craniomaxillofacial trauma cases using submental intubation. Methods: Datasheets of 14 craniomaxillofacial trauma cases who were intubated with submental intubation method were reviewed. The factors like: ease of anaesthesiologist for carrying out general anaesthesia, ease of surgeon for performing surgery and average time taken during the procedure, intraoperative and postoperative complications were evaluated and charted. Results: Submental intubation provides intraoperative airway control, avoids use of both oral and nasal routes, and allows intraoperative manipulation of occlusion, intramaxillary and intermaxillary fixation. This technique has minimal complications and has better patient, anaesthetists and surgeons acceptability. The limitations of this technique include longer preparation time, inability to maintain long term postoperative ventilation and unfamiliarity of technique itself. Conclusions: This submental intubation can be used with little modifications in a variety of complicated panfacial trauma cases.